Comunicología Y Unidad Iberoamericana - Ortiz Veas, Manuel (Re-presentaciones: Periodismo, comunicación y sociedad, 2007)
In this paper-"Communicology and iberian-American Unity"-Communication is COM ICA CION, etymological and lexicogenesys concepts. We are glad to invite you to think thoughtfully about different conceptions of Wentalschauung and a new vision ot it. Also we are calling to create a human com- munication science refered to observation of acts of doing together and participation in common and the possibility to make differences between the concepts of: data, information, to know, knowledge, meaning and senses.